Islamic students’ attitudes and perceptions toward learning English: a study from male-female students of STIT Madani Yogyakarta - Dhian Marita Sari (At Turots: Jurnal Pendidikan Islam, 2021)
The English status of a Foreign Language (FL) in Indonesia has been granted. However, the language has become quite popular and dominant in several schools in Indonesia, especially in private colleges and universities. The study aimed was to find out the male-female English foreign language (EFL) students’ attitudes and perceptions toward learning English and female and male students’ difficulties in learning English. The data was collected from 30 Islamic at the first student’s semester at STITMA Yogyakarta. Data collecting techniques used in this research were through a set of close-ended questioners. The study used a qualitative and quantitative resign design. The research finding revealed that male and female Islamic education students have positive attitudes and perceptions to learn English although the male students had lower enthusiasm to gain their knowledge in learning English than female students. Both (male and female students) perceived learning English was important not only for their future life but also for spreading Islam around the world. The female and male students had similar obstacles in pronunciation and vocabulary mastery. Moreover, most female students thought that speaking skills were the most difficult skill, while most male students consider listening was the most difficult skill to learn.